2000
DOI: 10.1128/mcb.20.3.760-769.2000
|View full text |Cite
|
Sign up to set email alerts
|

HuR Regulates p21 mRNA Stabilization by UV Light

Abstract: Expression of the cyclin-dependent kinase inhibitor p21 is highly induced by many stresses, including exposure to short-wavelength UV light (UVC), which increases p21 mRNA stability. Investigation into the mechanisms underlying this stabilization process revealed that proteins present in cytoplasmic lysates of human RKO colorectal carcinoma cells formed complexes with p21 mRNA that were inducible by treatment with UVC and other stress agents. The ubiquitous Elav-type RNA-binding protein HuR was identified with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

42
578
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 504 publications
(624 citation statements)
references
References 68 publications
42
578
3
1
Order By: Relevance
“…HuR has been found to interact with several AREs in vitro and in cells, and its overexpression induced stabilization of mRNAs for vascular endothelial growth factor (23), nitric oxide synthase II (35), eotaxin (1), and different ARE-containing reporter RNAs (14,15,33). Furthermore, suppression of HuR amounts by antisense RNA or small interfering RNA approaches inhibited stabilization induced by hypoxia (23), cytokines (35), or UV light (43) or during cell cycle progression (42). Most recently, constitutively active MK2 (41), as well as stimuli known to activate the p38/MK2 pathway (H 2 O 2 [41] and TNF-␣ [1]), was found to induce cytoplasmic accumulation of HuR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HuR has been found to interact with several AREs in vitro and in cells, and its overexpression induced stabilization of mRNAs for vascular endothelial growth factor (23), nitric oxide synthase II (35), eotaxin (1), and different ARE-containing reporter RNAs (14,15,33). Furthermore, suppression of HuR amounts by antisense RNA or small interfering RNA approaches inhibited stabilization induced by hypoxia (23), cytokines (35), or UV light (43) or during cell cycle progression (42). Most recently, constitutively active MK2 (41), as well as stimuli known to activate the p38/MK2 pathway (H 2 O 2 [41] and TNF-␣ [1]), was found to induce cytoplasmic accumulation of HuR.…”
Section: Discussionmentioning
confidence: 99%
“…HuR is a ubiquitously expressed member of the human ELAV family of RNA binding proteins (24) whose functional role in the stabilization of several ARE-containing mRNAs has been established (15,23,33,35,42,43). It also plays a role in the nuclear export of mRNA (17) and in control of translation (20,26).…”
mentioning
confidence: 99%
“…Recent studies have shown that mitogenic-activated protein kinase-2 increased cytoplasmic translocation of HuR and the stability of ARE-containing mRNAs (19). The translocation of HuR to the cytoplasm can be induced by stress caused by agents such as UV light, DNA damaging agents or T cell activation, while AMP-activated kinase can inhibit the translocation of HuR to the cytoplasm (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…14 HuR is a ubiquitous protein belonging to the embryonic lethal abnormal vision family of RNA-binding proteins, predominantly nuclear proteins, which shuttle between the nucleus and cytoplasm. HuR regulates cyclin A, cyclin B1, 15 and p21 16 mRNA stability during cell proliferation. AUF1, a member of the heteronuclear ribonucleoprotein (hnRNP) family (also known as hnRNP D), is another RNA-binding protein, which exists in four isoforms (37, 40, 42, and 45 kDa).…”
Section: See Page 2582mentioning
confidence: 99%